Implementasi Layanan Bimbingan Konseling untuk Mengatasi Kesulitan Belajar Peserta Didik di SD Negeri Sambi 1 Tahun 2016/2017 - Utami, Hening Budi; , Prof. Dr. Harun Joko Prayitno, M.Hum (2017)
This research was made for to know kinds of learning disability s, to know cause factor of learningdisability, to describe how the teacher overcome learning disability by used guidance conselling services. This research included in qualitative research with the phenomenology research design. The method in this research is interview, observation, and documentation. Analysis by using qualitative analysis, is the data that described with the words or sentences and than made the conclusion by using the steps, reduction the data, present the data, and get the conclusion. The result of the research showed if in SD Negeri Sambi 1 there was a guidance conselling included. Tutoring services for the learnes teacher as implementers has already gives the tutoring to the learnes who find the disability s. The expectation of guidance conselling is the learnes capable to optimize their achievement. Keyword : guidance, conseling, learning disability